National digitalization programs in European Union: experience for Ukraine - Sheiko, I.; Storozhenko, O. (Kielce, Poland: Baltija Publishing, 2019)
The development of the digital economy and society of Ukraine is a crucial factor for the success of not only all reforms, but also Ukrainian business on the world stage. Ukraine is an important player in the global digital market, but unfortunately, solely as an exporter of IT services and brains. High developed traditional sectors can be a good basis for providing elements of digitalization
Keywords: innovation; digitalization; industrial policy; tax reform; ukrainian roadmap